Acyl-chain elongation drives ketosynthase substrate selectivity in trans-acyltransferase polyketide synthases - Jenner, Matthew; Afonso, José Pedro; Bailey, Hannah R.; Frank, Sarah; Kampa, Annette; Piel, Jörn; Oldfield, Neil J. (Wiley-VCH Verlag, 2015)
Type I modular polyketide synthases (PKSs), responsible for the biosynthesis of many biologically active agents, possess a ketosynthase (KS) domain within each module to catalyze chain elongation. Acylation of the KS active site Cys residue is followed by transfer to malonyl-acyl carrier protein, yielding an extended β-ketoacyl chain. To date, the precise contribution of KS selectivity in controlling product fidelity has been unclear. We submitted six KS domains from the trans-acyl transferase PKSs to a mass spectrometry-basedelongation assay, and identified higher substrat selectivity in the elongating step than in preceding acylation. A close correspondence between observed KS selectivity and that predicted by phylogenetic analysis was seen. Our findings provide insights into the mechanism of KS selectivity in this important group of PKSs, can serve as guidance for engineering, and show that targeted mutagenesis can be used to expand the repertoire of acceptable substrates.